Review of the book "La educación es política" by Jaume Carbonell Sebarroja - Totoricagüena Barandica, Karmele (Avances en Supervisión Educativa, 2019)
LA EDUCACIÓN ES POLÍTICA Author: Jaume Carbonell Sebarroja Original title: L’educació és política Translated from Catalan: Manuel León Urrutia. Ediciones Octaedro, S.L. Collection: Educational resources / The Journal of Education First edition: January 2019 Soft cover: 224 pages ISBN-10: 8417667032 ISBN-13: 978-8417667030 Author of the review: Karmele Totoricagüena Barandica Education Inspector of Euskadi